PENGEMBANGAN AUDIO PEMBELAJARAN UNTUK MENINGKATKAN PEMAHAMAN ALIH KODE DAN CAMPUR KODE DENGAN MENGGUNAKAN MODEL JIGSAW PADA MAHASISWA JURUSAN BAHASA DAN SASTRA INDONESIA - Inayah Hanum (LPPM Universitas Negeri Medan, 2014)
The aim of this study is to improve students’ understanding on code switching and code mixing through jigsaw model by using audio learning media. Cycle 1 is conducted by using audio learning media through jigsaw model. If the final score is not satisfied, it will be continued to cycle II. The instrument for this study is essay test and classroom observation.The participant is 50 students of Indonesia Department who take Sociolinguistics subject, 27 students from regular class and 23 students from extension class. From analyzing the data, it is found that the score of preminairy data is 68,05, meanwhile the score in cycle 1 is 82,5 and in cycle 2 is 93,7. As a result 50 students has improved their understanding 18% categorized as good and 82 % categorized as very good. The conclusion of this study is students’ understanding on code switching and cod mixing has improved through audio learning media with jigsaw model.Keywords: Model, Audio, Jigsaw, Campur Kode, Alih Kode